Cytotoxic and genotoxic studies of crude extracts from the leaves, stems and roots of Tulbaghia Violacea - Nellvecia, Madike Lerato (Vaal University of Technology, 2017)
Tulbaghia violacea Harv. (wild garlic) has been used in traditional medicine in Southern Africa for the treatment of various ailments. Despite the widespread use and popularity of this medicinal plant as a herbal medicine, there is contradictory evidence regarding the safety and toxicity of the plant. The phytochemical profiling of the plant has also been neglected in research. The determination of chemical constituents present in plant material as well as the potential toxicity found in plants are preliminary steps necessary for the discovery and development of novel therapeutic agents with improved efficacy. The aim of this study was to evaluate the cytotoxic and genotoxic potential of crude extracts from the leaves, stems and roots of T. violacea. This was performed in vitro using aqueous and ethanol extracts of the leaves, stems and roots. The aim of the study was achieved by three major objectives; (1) to identify the active phytocompounds present in the leaves, stems and roots, (2) to assess the cytotoxicity using the MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) cell proliferation assay, and (3) to evaluate the genotoxic potential of the leaf, stem and root water extracts using the Allium cepa assay. A total of 14 phytochemicals were each extracted separately with distilled water and 70% ethanol by maceration from the leaves, stem and roots of T. violacea. The results of the qualitative phytochemical analysis showed that pharmacologically active compounds such as tannins, terpenoids, flavonoids, saponins, proteins, steroids, cardiac glycosides, phenols and coumarins were present in some organs of T. violacea. However, phlobatannins, leucoanthocyanins, alkaloids, carbohydrates and anthocyanins were absent in all plant parts. Overall, the leaves of the plant contained more active compounds than those present in the stems and roots when both water and 70% ethanol were used as the extractants. The quantitative phytochemical analysis for the Total Flavonoids Content (TFC) and Total Phenolic Contents (TPC) was also assessed. The water (0.027 mg/g) and 70% ethanol (0.053 mg/g) were most effective in extracting flavonoids from the leaves while the least amounts were obtained from the stems and roots. This observation was similar to the TFC were the water extracts of the leaves were the most effective in extracting phenols followed by the stems and roots. The MTT assay was conducted using two cell lines RAW 264.7 and C2C12. The experiment was conducted in triplicates for the leaf, stem and root extracts (water and ethanol) of T. violacea. The experimental design employed a 23 factorial design where three independent variables (concentration, incubation time and type of extracts) were selected using two levels for each variable (high (+) and low (-)). The results illustrated that both the water and ethanol extracts only showed a significant reduction in the number of viable cells at the concentration higher than 250 μg/ml treatment for both RAW 264.7 and C2C12 cells. The ethanol extracts from the leaves, stems and roots were found to be toxic towards the RAW 264.7 cells even at lower concentrations at both 24 and 48 h incubation periods (% cell viability < 50%). The water extracts were non-toxic to RAW 264.7 cells except for the water stem extract which showed toxicity after 48 h incubation (IC50 = 9.475 (4.061 to 23.39)). For the C2C12 cells, the lowest potent toxic concentration was 250 μg/ml for the ethanol extract of the stem after 48 h incubation. Overall, the T. violacea plant extracts were non-toxic as percentage cell viability greater than 50% was noted for both extraction solvents in all the plant parts of T. violacea. No cytotoxic activity was observed in all T. violacea plant parts with the C2C12 cell line (IC50 > 30 μg/ml). For the Allium cepa assay, only the water crude extracts of the leaves, stems and roots of T. violacea were used. A similar trend of potent genotoxic activity in the water stem extracts compared to the leaf and root extracts at the concentration ranges studied. Similar to the MTT assay, it is clear from the study that at higher concentrations, the water crude extracts from the leaves, stems and roots of T. violacea is toxic. From this study, it can be concluded that the extraction of compounds using water is more efficient than using ethanol. Overall, the T. violacea leaf extracts extracted the most phytocompounds and showed the highest percentage of viable cells as well as desirable IC50 values. However, preparation of herbal remedies using T. violacea plant extracts should be done with caution due to their possible genotoxic and cytotoxic potential at higher concentrations. This study raises a need to further conduct in vivo cytogenetic studies to ascertain the possible toxic effects of T. violacea crude extracts.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Science), Vaal University of Technology.
Keywords: 2/3 Factorial design; Allium cepa assay; C2C12 cells; MTT cell proliferation assay; Phytocompounds; RAW 264.7 cells; Total Flavonoids Content (TFC); Total Phenolic Contents (TPC); Tulbaghia violacea; Liliaceae.; Garlic.; Plants -- Analysis.; Medicinal plants.; Dissertations, Academic -- South Africa.